Differentiation of Human Induced Pluripotent Stem Cell (hiPSC)-Derived Neurons in Mouse Hippocampal Slice Cultures - Hiragi, Toshimitsu; Andoh, Megumi; Araki, Toshihiro; Shirakawa, Takayuki; Ono, Takashi; Koyama, Ryuta; Ikegaya, Yuji (Frontiers in Cellular Neuroscience, 2017)
Potential clinical applications of neurons derived from human induced pluripotent stem cells (hiPSC-neurons) for drug screening and transplantation therapies have received considerable attention. However, it remains unclear whether and how transplanted hiPSC-neurons are incorporated into pre-existing neural circuits. Here we developed a co-culture system of hiPSC-neurons and mouse hippocampal slices to examine the differentiation of hiPSC-neurons in pre-existing neural circuits. hiPSC-neurons transplanted in mouse hippocampal slices expressed the hippocampal neuron-specific markers HuB and Prox1 after 7 days of culture, while those markers were scarcely expressed in hiPSC-neurons cultured on glass dishes. Furthermore, hiPSC-neurons transplanted in the dentate gyrus of slice cultures grew to exhibit dentate granule cell-like morphologies, including besom-shaped dendrites. Similarly, hiPSC-neurons transplanted in the CA1 region of slice cultures grew to exhibit CA1 pyramidal cell-like morphologies, including primary apical and multiple basal dendrites with synaptic spines. Additionally, these cells projected axons toward the entorhinal cortex as observed in vivo. These data suggest that hiPSC-neurons were anatomically integrated into pre-existing neural circuits in a region-specific manner. Thus, the co-culture system will be useful for the study of efficient strategies to differentiate transplanted hiPSC-neurons.